A genealogy of what nurses know about 'the good death': A socio‐materialist perspective. (24th August 2021) - Rushton, Carole; Edvardsson, David
Abstract: In this article, we report the outcome of a sociological inquiry into nursing knowledge of death and dying, specifically 'the good death'. A genealogical approach informed by actor‐network theory and appreciative inquiry were used to compose a broad socio‐material account of how nurses concern themselves with the care of the dying and end‐of‐life care. Our enquiry revealed similarly to other studies, that there was no shared or overarching model of care. Key themes derived from nurses' translations of 'the good death' were re‐presented pictorially as six pillars and two processes to comprise a new diagram of The Personalised Ideal Death.